Answer: 2.76 g
Step-by-step explanation:
The formula to find the standard deviation:-
![\sigma=\sqrt{\dfrac{\sum(x_i-\overline{x})^2}{n}}](https://tex.z-dn.net/?f=%5Csigma%3D%5Csqrt%7B%5Cdfrac%7B%5Csum%28x_i-%5Coverline%7Bx%7D%29%5E2%7D%7Bn%7D%7D)
The given data values : 560 g, 562 g, 556 g, 558 g, 560 g, 556 g, 559 g, 561 g, 565 g, 563 g.
Then, ![\overline{x}=\dfrac{\sum_{i=1}^{10} x_i}{n}\\\\\Rightarrow\ \overline{x}=\dfrac{560+562+556+558+560+556+559+561+565+563}{10}\\\\\Rightarrow\ \overline{x}=\dfrac{5600}{10}=560](https://tex.z-dn.net/?f=%5Coverline%7Bx%7D%3D%5Cdfrac%7B%5Csum_%7Bi%3D1%7D%5E%7B10%7D%20x_i%7D%7Bn%7D%5C%5C%5C%5C%5CRightarrow%5C%20%5Coverline%7Bx%7D%3D%5Cdfrac%7B560%2B562%2B556%2B558%2B560%2B556%2B559%2B561%2B565%2B563%7D%7B10%7D%5C%5C%5C%5C%5CRightarrow%5C%20%5Coverline%7Bx%7D%3D%5Cdfrac%7B5600%7D%7B10%7D%3D560)
Now, ![\sum_{i=1}^{10}(x_i-\overline{x})^2=0^2+2^2+(-4)^2+(-2)^2+0^2+(-4)^2+(-1)^2+1^2+5^2+3^2\\\\\Rightarrow\ \sum_{i=1}^{10}(x_i-\overline{x})^2=76](https://tex.z-dn.net/?f=%5Csum_%7Bi%3D1%7D%5E%7B10%7D%28x_i-%5Coverline%7Bx%7D%29%5E2%3D0%5E2%2B2%5E2%2B%28-4%29%5E2%2B%28-2%29%5E2%2B0%5E2%2B%28-4%29%5E2%2B%28-1%29%5E2%2B1%5E2%2B5%5E2%2B3%5E2%5C%5C%5C%5C%5CRightarrow%5C%20%5Csum_%7Bi%3D1%7D%5E%7B10%7D%28x_i-%5Coverline%7Bx%7D%29%5E2%3D76)
Then, ![\sigma=\sqrt{\dfrac{76}{10}}=\sqrt{7.6}=2.76](https://tex.z-dn.net/?f=%5Csigma%3D%5Csqrt%7B%5Cdfrac%7B76%7D%7B10%7D%7D%3D%5Csqrt%7B7.6%7D%3D2.76)
Hence, the standard deviation of his measurements = 2.76 g
Answer: Is It 40? I cant really do this on paper sorry too many multiplication steps
Step-by-step explanation:
Sorry im just very confused but I tried my best
Answer:
Final answer is
and
.
Step-by-step explanation:
Given equation is
.
Now we need to solve that by factoring.
![9x^2+24x+20=4](https://tex.z-dn.net/?f=9x%5E2%2B24x%2B20%3D4)
![9x^2+24x+20-4=0](https://tex.z-dn.net/?f=9x%5E2%2B24x%2B20-4%3D0)
![9x^2+24x+16=0](https://tex.z-dn.net/?f=9x%5E2%2B24x%2B16%3D0)
![9x^2+12x+12x+16=0](https://tex.z-dn.net/?f=9x%5E2%2B12x%2B12x%2B16%3D0)
![3x(3x+4)+4(3x+4)=0](https://tex.z-dn.net/?f=3x%283x%2B4%29%2B4%283x%2B4%29%3D0)
![(3x+4)(3x+4)=0](https://tex.z-dn.net/?f=%283x%2B4%29%283x%2B4%29%3D0)
, ![(3x+4)=0](https://tex.z-dn.net/?f=%283x%2B4%29%3D0)
, ![3x+4=0](https://tex.z-dn.net/?f=3x%2B4%3D0)
, ![3x=-4](https://tex.z-dn.net/?f=3x%3D-4)
, ![x=-\frac{4}{3}](https://tex.z-dn.net/?f=x%3D-%5Cfrac%7B4%7D%7B3%7D)
Hence final answer is
and
.